DAMPAK INSENTIF PAJAK PERUMAHAN TERHADAP POTENSI PENERIMAAN PAJAK NEGARA DAN PENINGKATAN PENDAPATAN MASYARAKAT: KASUS PROVINSI SULAWESI SELATAN - Towaf Totok Irawan (Jurnal Ilmiah Manajemen dan Bisnis, 2016)
Until now the government and private sector have not been able to address the backlogof 13.5 million housing units for ownership status and 7.6 million units for residentialstatus. The high price of land has led to the high price of the house, so that lowincomecommunities (MBR) is not able to reach out to make a home purchase. In addition to thehigh price of land, tax factors also contribute to the high price of the house. Thegovernment plans to issue a policy for the provision of tax incentives, ie abolish VAT onhomeforming material transaction. This policy is expected to house prices becomecheaper, so the demand for housing increases, and encourage the relevant sectors tointensify its role in the construction of houses. It is expected to replace the lost taxpotential and increase incomes. Analysis of the impact of tax incentives housing topotential state revenue and an increase in people's income, especially in South Sulawesiprovince is using the table IO because in addition to looking at the role each sector canalso see the impact on taxes (income tax 21 Pph 25Pph, VAT), and incomes (wage).Althoughintheshorttermimpactisstillsmall,butveryrewardinginthelongrun.